The Relationship Between Fetuin-A and Glycemic Control in Women with Polycystic Ovary Syndrome in Babylon Province - Tuqa Hazem Abdallah,; Zinah Abbass Ali,; Suha Jasim Witwit, (American Journal of Biology and Natural Sciences, 2026)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders affecting women of reproductive age and is strongly associated with insulin resistance and infertility. This study aimed to evaluate serum Fetuin-A levels and their relationship with glycemic control and reproductive hormones in women with PCOS. A case-control study was conducted on 90 women aged 18–44 years in Babylon Province, Iraq. Participants were divided into two groups: 45 obese infertile women diagnosed with PCOS and 45 healthy controls. Serum levels of Fetuin-A, kisspeptin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), fasting insulin, and fasting blood glucose were measured using ELISA techniques. Insulin resistance was assessed using the homeostatic model assessment (HOMA-IR).The results revealed a significant increase in serum Fetuin-A, fasting insulin, LH, HOMA-IR, and LH/FSH ratio in PCOS patients compared with controls (P < 0.05). In contrast, kisspeptin and FSH levels were significantly decreased. Fetuin-A showed a strong positive correlation with fasting insulin and HOMA-IR and a significant negative correlation with kisspeptin. In conclusion, elevated Fetuin-A levels are closely associated with insulin resistance and hormonal imbalance in PCOS, suggesting its potential role as a biomarker in the pathogenesis of the syndrome.